Study on the Effect of Overflowing length on the Water Quality and Soil Physical Properties of Andosol together with Tomato Plant Growth (Lycopersicum esculentum Mill.) - Anugrah Aqsra Bandi; Sumono Sumono; Achwil Putra Munir (Universitas Sumatera Utara, 2014)
Flooding and overflowing on horticultural plant especially for tomato plants cause failure of vegetative and generative growth.The extent to which tomato plants tolerance if grown in andosol soil to overflowing and flooding need to be studied. This research was aimed to examine the Effect of Overflowing length on the water quality and soil physical properties of andosol together with tomatoe plant growth. The result of the research showed that evapotranspiration at beginning of growth of 15 days since plant (dsp) was 1,79 mm/day, on active growth (16-45 dsp) was 3,45 mm/day, on maximum growth (46-75 dsp) was 3,45 mm/day and the end of growth (>75 dsp) was 2,41 mm/day. Water quality that unfavorable effect towards the growth of tomato plants for 2 days in overflowed conditions and overflowed until the plants death was dissolved oxygen. Dissolved oxygen for 2 days in overflowed conditions was 1,98 ppm and for overflowed conditions until the plants death was 1,68 ppm.Soil Physical properties that unfavorable effect towards the growth of tomato plants for all conditions was soil temprature. Soil temprature for 2 days in overflowed conditions was 27,83oC, for overflowed conditions until the plants death was 28,25oC and for spacey capacity conditions was 27,85oC. For 2 days in overflowed conditions the soil salinity was over the restriction limit which was 5,8 mS/cm. Blossom production of tomato plant on spacey capacity conditions was 27 blossom/plant, for 2 days in overflowed conditions was 17 blossom/plant and for overflowed conditions until the plants death has not blossom. Key word : overflowing, tomato plants, water quality, soil physical properties